Gestational Age-Specific Complete Blood Count Signatures in Necrotizing Enterocolitis - Pantalone, Julia M.; Liu, Silvia; Olaloye, Oluwabunmi O.; Prochaska, Erica C.; Yanowitz, Toby; Riley, Melissa M.; Buland, Justin R.; Brozanski, Beverly S.; Good, Misty; Konnikova, Liza (Frontiers in Pediatrics, 2021)
Objective: Necrotizing enterocolitis (NEC) is characterized by peripheral cell abnormalities, yet few studies have analyzed the complete blood count (CBC) specifically by gestational age (GA). Our objective was to describe GA-specific immune abnormalities in NEC through a comprehensive analysis of the CBC differential. Methods: Using a cohort of 246 infants (177 cases, 69 controls) admitted to neonatal intensive care units at a single institution, we retrospectively analyzed CBCs around illness onset in NEC cases compared to controls. Cases included surgical NEC (S-NEC, 34.5%) and medical NEC (M-NEC, 65.5%). Infants were divided into those born at GA <33 weeks (w) and ≥33w. Differences in CBC values were described as percent change at NEC onset from baseline and percent change at antibiotic completion after NEC. We used machine learning algorithms based on the CBC at NEC to generate predictive models for diagnosis. Results: At NEC onset, there was an acute drop in monocytes and lymphocytes along with a rise in bands in S-NEC infants born <33w compared to M-NEC. In comparison, both M-NEC and S-NEC ≥33w had a drop in neutrophils at diagnosis compared to controls. At antibiotic completion, monocytes in S-NEC <33w significantly rose compared to M-NEC; yet for S-NEC ≥33w, bands significantly dropped compared to M-NEC. Predictive modeling was able to accurately predict S-NEC from M-NEC and controls. Conclusion: There are discrete leukocyte patterns in NEC based on GA. The CBC at diagnosis may be useful in identifying patients who will require surgery.